PENGEMBANGAN WEBSITE JII-ANALISA.COM SEBAGAI ALAT ANALISIS TIPOLOGI SAHAM SYARIAH DI INDONESIA - Aulia Faqih Rifa'i; Mohammad Farhan Qudratullah; Riyanto Riyanto (Integrated Lab Journal, 2018)
This research aims to develop a website JII-Analisa.com as typology’s analytical tool of sharia stock in Indonesia. The development of JII-Analisa.com using SDLC (System Development Life Cycle) which consists of 5 (five) steps; website’s strategic planning, determine the scope of website, website’s requirements analysis, design and implementations of website, and testing. The results of this research is JII-Analisa.com been developed successfully as a typology analytical tool of sharia stock joined in the Jakarta Islamic Index (JII). For the periode December 11, 2015 until June 11, 2016 (6 months) there are 4 (four) shares that can be used as a portfolio’s candidate; they are ADRO, PTBA, INDF, and ICBP.